1975
DOI: 10.1021/jf60201a016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of environmental distribution and fate of hexachlorocyclopentadiene, chlordene, heptachlor, and heptachlor epoxide in a laboratory model ecosystem

Abstract: The distribution and fate of [14C]heptachlor and the organochlorine compounds closely associated with it in manufacture and use, hexachlorocyclopentadiene, chlordene, and heptachlor epoxide, have been evaluated in food chain organisms in two laboratory model ecosystems and in vitro by sheep liver microsomes. Chlordene and heptachlor undergo epoxidation rapidly and are also hydroxylated at Ci to form the corresponding hydroxy analogs. Heptachlor epoxide, however, is highly stable in biological systems. The rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

1977
1977
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 14 publications
1
24
0
Order By: Relevance
“…Transformation of heptachlor to heptachlor epoxide in liquid culture was evaluated and showed that its metabolite was mostly found in 50 μg/mL heptachlor treatments or 27.85% of parent heptachlor with the positive values of redox potential suggesting the oxidative activities of microorganisms. Lu et al [54] reported the transformation of heptachlor into 1-hydroxychlordene and 1-hydroxychlordene epoxide was relatively rapid but small proportion of heptachlor epoxide was formed which suggested that heptachlor epoxide formed environmentally largely in vivo by microsomal multifunction oxidase action.…”
Section: The Effects Of Initial Concentrations Of Heptachlor On Micromentioning
confidence: 99%
See 1 more Smart Citation
“…Transformation of heptachlor to heptachlor epoxide in liquid culture was evaluated and showed that its metabolite was mostly found in 50 μg/mL heptachlor treatments or 27.85% of parent heptachlor with the positive values of redox potential suggesting the oxidative activities of microorganisms. Lu et al [54] reported the transformation of heptachlor into 1-hydroxychlordene and 1-hydroxychlordene epoxide was relatively rapid but small proportion of heptachlor epoxide was formed which suggested that heptachlor epoxide formed environmentally largely in vivo by microsomal multifunction oxidase action.…”
Section: The Effects Of Initial Concentrations Of Heptachlor On Micromentioning
confidence: 99%
“…Many studies reported that the temperature of 30°C was suitable for chemical biodegradation including biodegradation of HCH isomer in soil slurry [57] and DDT and heptachlor degradation in river sediment of Taiwan [56]. Moreover, biodegradation of endosulfan by soil bacteria [68], abiotic degradation of endosulfan in a clay soil [70] and degradation of DDT by soil bacteria [54] yielded the maximum values at temperature of 30°C. However, microorganisms have the ability to degraded pesticides in a wide range of temperatures.…”
Section: Effect Of Incubation Temperature On Heptachlor Degradationmentioning
confidence: 99%
“…Heptachlor epoxide is more toxic than heptachlor in animals. Hep'achlor is also hydrolyzed to 1-hydroxy-4,5,6,7,8,8-hexachloro-3a,4,7,7a-tetrahydro-4,5-methanoindene, which is then converted to tne epoxide (Lu et al, 1975).…”
Section: Toxicokineticsmentioning
confidence: 99%
“…Heptachlor exo-epoxide (hereafter called HEPX) is more stable than heptachlor in ecosystems (Lu et al, 1975), and can still be detected in soils (Aigner et al, 1998;Bidleman et al 2006;…”
Section: Introductionmentioning
confidence: 99%